IN PRINCIPLE YES, IN APPLICATION, NO; RWANDAN NURSES’ SUPPORT FOR INTERGRATION OF MENTAL HEALTH SERVICES - Vedaste, Baziga; Smith, Amanda April Heather (Africa Journal of Nursing and Midwifery, 2016)
Mental ill-health contributes significantly to the global burden of disease as the fourth leading cause of global disability. To reduce this burden, by aiming at reduction of the treatment gap, the World Health Organisation recommended integration of mental health care into general health care structures, and deinstitutionalization coupled with community re-integration. Given the distribution of mental health professionals in Sub Sahara Africa the implementation of such integration is largely the work of nurses, specifically non mental health specialist nurses. Previous African studies report nurses difficulties with this integration; lack of preparation, knowledge, expertise, and time. Mental illness stigma is suggested to underscore a large portion of these difficulties. This quantitative study used a cross sectional survey approach to gather mental illness stigma related data from nurses (N=104, n=102) working within in a district hospital in Rwanda. A self-report questionnaire included person variables (age, gender, nursing experience, nursing qualification and category of nurse) and two scales; Level of Contact Scale (LOC), and Community Attitudes towards Mental Illness Scale - Swedish version (CAMI-S). Results support previous research regarding the type and extent of mental illness stereotypes, and mediating effects of familiarity. Significant associations between mental illness stereotypes and; younger and the less experienced nurses were also reported. However, the extent of contradiction within participant responses on the CAMI-S, across all demographics variables, suggests significant tension between nurses desire to subscribe to a nursing and national ideology of non-discrimination, a cherished value within the Rwandan context, and their fears associated with their stereotypical beliefs. In addition to the continued use of contact within health care worker training programs and clinical placements it is recommended that supportive interventions be implemented that are narrative in nature and facilitate the resolution of tension between ‘what I should believe’ and ‘what I do believe’. Key words: mental illness stereotypes, community based care, nurse, Rwanda